A demand side perspective on the importance of representative bureaucracy AIDS, ethnicity, gender and sexual orientation. - Thielemann, Gregory S.; Stewart, Joseph, Jr. (1996)
"Is there a demand for a representative bureaucracy? Prior research on representative bureaucracy assumes that it is a good to be supplied that will result in a better-served, more-satisfied clientele. If anyone should care about the representativeness of a service delivery agency, it should be persons living with AIDS (PLWAs), whose lives can be extended and improved by taking advantage of services offered. Gregory S. Thielemann and Joseph Stewart, Jr., surveyed 510 PLWAs in Dallas and found that, although there are some significant differences between groups, PLWAs clearly exhibit a demand for a representative bureaucracy particularly among personnel who actually provide services. These findings demonstrate the importance of representative bureaucracy and have implications specifically for the provision of AIDS services"
Keywords: Civil service - United States; Bureaucracy